The Impact of Ownership Structure and Capital Structure on Firm Performance: Evidence from China GEM - Wang, Huixin (2020)
Purpose: This study researches the relationship between ownership structure, capital structure and corporate performance of the companies listed on the China Growth Enterprise Market (GEM).